Peningkatan Sanitasi Sekolah Dasar di SDN 10 dan 17 Mata Air Timur, Kelurahan Mata Air, Padang, Sumatera Barat - Fitriyani Fitriyani; Machranda Machranda; Putri Andini; Lieona Fibra Asha; Asha Firnandia; Putri Ramadhani; Mido Irawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2022)
Public places can become a place for disease transmission, environmental pollution, or other health problems, so it is mandatory to carry out environmental sanitation. Sanitation in schools is an important thing to implement currently. Students are not only taught in class about sanitation, but students are expected to practice the theory they have learned in class. Problems that often arise are related to school sanitation, such as having poorly maintained latrines or little water so that it is not used optimally. Based on this problem, sanitation improvement was carried out using outreach and education methods interspersed with pre-tests and post-tests at SDN 10 and 17 Mata Air Timur, Padang, West Sumatra. Based on the pre-test and post-test, it can be concluded that elementary school student's knowledge of school sanitation has increased. It is hoped that the school will improve School Medical Room (UKS) to provide support, both in the form of providing facilities and infrastructure, as well as moral support. The Public Health Centers could also support improving sanitation by monitoring and coaching teachers and the school environment.